The institutional primary healthcare service quality and patients' experiences in Chinese community health centres: results from the Greater Bay Area study, China - RuQing Liu; Leiyu Shi; YiFan Meng; Ning He; JingLan Wu; XinWen Yan; RuWei Hu (BMC, 2021)
Abstract Background The goal of this paper was to assess the quality of primary healthcare services at community health centres (CHCs) from the demand (patient) and supplier (healthcare service institution) angles. Methods This study was conducted at six CHCs in the Greater Bay Area of China. Between August and October 2019, 1,568 patients were recruited (55.8% women and 44.2% men). We evaluated the service quality of CHCs using the National Committee for Quality Assurance Patient-Centred Medical Home (NCQA-PCMH) recognition questionnaire. We assessed patients' experiences with medical and health services using the Primary Care Assessment Tools (PCAT). Results PCAT total and sub-domains scores were significantly difference at the six CHCs (P < 0.001). Among the six CHCs, Shayuan CHC had the highest PCAT total and sub-domain scores and the highest NCQA-PCMH total and sub-domain scores, as well. Older (> 60 years), female, lower education, and employee medical-insured individuals had better patient experiences. Conclusions Our results indicate that CHCs could improve their service quality by improving both institutional health service quality based on NCQA-PCMH assessment and patient experiences based on PCAT scales. These findings can help inform patient-centred primary healthcare policy and management.